A REVIEW OF PT GOTO Tbk FINANCIAL PERFORMANCE BEFORE AND AFTER THE MERGER - Iftahul Mufarrica; Fida Oktafiani (SEAN Institute, 2023)
This review examines the financial performance of PT GOTO Tbk, a prominent Indonesian digital technology company formed through the merger of Gojek and Tokopedia. In the context of today's competitive business landscape, mergers have emerged as common strategies for growth and competitiveness. Asian markets, driven by technological demands, have witnessed a surge in mergers aimed at enhancing business strength and achieving various goals, including synergy and strategic advantages. The study evaluates PT GOTO Tbk's financial performance by analyzing key financial metrics such as capital adequacy, liquidity, profitability, and financial ratios, including Current Ratio, Return On Assets, Return On Equity, Debt to Asset Ratio, Net Profit Margin, Total Asset Turnover, and Earnings Per Share. These metrics provide valuable insights into the company's financial health and how it has been affected by the merger. Through a comprehensive analysis, this review seeks to shed light on how mergers can impact a company's financial performance, offering a nuanced understanding of the changes observed in these key financial indicators before and after the merger. Ultimately, the findings contribute to the broader discourse on mergers and their effects on the financial well-being of companies in dynamic markets. In today's competitive business environment, innovation and strategic thinking are essential for a company's survival. Mergers, both internal and external, have become common strategies for growth, particularly in Asian markets driven by technological advancements. These mergers aim to strengthen businesses by achieving synergies, strategic advantages, and improved effectiveness. However, it's important to note that the benefits of mergers may take time to materialize, and they involve challenges and costs, necessitating careful decision-making. Assessing a company's financial health is crucial, and various metrics, such as capital adequacy, liquidity, and profitability, are used for this purpose. Financial ratios, including Current Ratio, Return On Assets, Return On Equity, Debt to Asset Ratio, Net Profit Margin, Total Asset Turnover, and Earnings Per Share, play a vital role in performance evaluation. A case study of PT. GOTO Tbk, a digital technology company resulting from the merger of Gojek and Tokopedia in Indonesia, demonstrates that mergers can have different effects on financial performance depending on specific metrics. This research supports the notion that mergers may have motives beyond enhancing financial performance, potentially aiming to improve human resource performance. The conclusion drawn is that there was no significant difference in PT. Goto Tbk's financial performance before and after the merger, possibly due to increased debt and losses resulting from extensive product diversification at the company.